Video Compression – from Fundamentals to H.264 and H.265 Standards (International Journal of Engineering and Computer Science, 2018)
In this era of modern technologies and Internet, Video Compression is extremely important for systematic storing and transmission of huge sized videos. In past two decades, there was a rapid development in the area of Video Compression Technology. To attain the best equilibrium between compression efficiency and perceptual quality, a number of video compression techniques have been developed.  The first part of this survey paper gives an overview about Video Compression. The latter part gives a summary about different Video Compression Standards.